MO053: Are Renal Prognostic Markers Different in Patients with Exostosin 1/2 Positive or Negative Membranous Lupus Nephritis? A Single Center Experience in Turkey. (3rd May 2022) - Ebru Eser, Zeynep; Turgutalp, Kenan; Karabulut, Yasemin; Akcali, Esra; Cagatay Kose, Emre; Ballı, Ebru; Bardak, Simge; Demir, Serap; Kıykım, Ahmet
Abstract: BACKGROUND AND AIMS: Recently, prognostic importance of antibodies in primary membranous nephropathy is well defined. However, knowledge about antibodies related to disease activity in membranous lupus nephritis (MLN) is limited. Exostosin1 and exostosin2 (EXT1/2) are novel antibodies detected in MLN, and further studies are needed for the prognostic significance of them as a marker. The aim of this study is to determine whether renal prognostic markers differ between EXT1/2 positive and negative MLN patients. METHOD: This is a single-center, retrospective and observational study. Class 5 MLN patients aged 18 or older were included in the study. Clinical characteristics, results of biochemical analysis and histopathological examination were recorded from 6 to 18 months. The end-point of the study was determined as complete remission, partial remission, need for renal replacement therapy (RRT) and exitus. Group 1: EXT1/2 positive patients. Group 2: EXT1/2 negative patients. Light, immunofluorescent and electron microscopy findings and laboratory parameters were evaluated in EXT1/2 positive and negative patients. RESULTS: Group 1: n  = 11 patients. Group 2: n  = 7 patients. The main demographic, biochemical and histopathological characteristics of the groups were shown in Table 1 . EXT1/2 negative patients, a higher number of sclerotic glomeruli, interstitial fibrosis and a higher amount of proteinuria were present than positive patients (P < 0.05). EXT1/EXT2 negative patients had significantly lower C3 and C4 levels than positive patients (P < 0.05). EXT1/EXT2 negative patients had a higher RRT or exitus rate within 18 months than positive patients (P < 0.05). In contrast, EXT1/EXT2 positive patients had a higher rate of achieving complete or partial remission within 18 months than negative patients (P < 0.05). The effect of immunosuppressive drug use other than steroids and glomerulosclerosis remission was statistically significant (P = 0.04 and P = 0.011). CONCLUSION: EXT1/2 negative class 5 LMN patients have more poor renal prognostic indicators than positive patients. RRT or exitus rate is higher in EXT1/EXT2 negative patients than positive patients. However, more randomized controlled studies are needed.